ChemInform Abstract: Catalytic Performance of Hydrophobic Sulfonated Nanocatalysts CMK‐5‐SO3H and SBA‐15‐Ph‐PrSO3H for Ecofriendly Synthesis of 2‐Substituted Benzimidazoles in Water. Issue 39 (September 2016) - Zareyee, Daryoush; Tuyehdarvary, Sakineh Rostamian; Allahgholipour, Leila; Hossaini, Zinatossadat; Khalilzadeh, Mohammad A.
Abstract: The title benzimidazoles are prepared from various aldehydes and benzenediamine under green reaction conditions.